The Legal Authority of Arbitral Awards in the Indonesian Judicial System: Reconciling Party Autonomy, Judicial Supervision, and Legal Certainty - Abdul Hakim; Dinda Ayu Arini Chaniago; Yara Shita; Wenni Nahdiani Tanjung (Jurnal Cendikia ISNU SU, 2026)
Arbitration has become an increasingly important mechanism for resolving commercial disputes due to its efficiency, finality, and procedural flexibility. Nevertheless, the legal force of arbitral awards within Indonesia's judicial system remains conceptually debated because such awards originate from private agreements while simultaneously requiring judicial recognition and enforcement under public law. Existing scholarship has predominantly examined arbitral awards from procedural perspectives, particularly regarding enforcement and annulment, with limited attention to the institutional foundations that determine their legal authority. This study aims to analyze the legal force of arbitral awards within Indonesia's judicial system and to reconstruct the interaction between contractual autonomy, judicial supervision, and statutory legitimacy in determining their binding effect. Employing normative legal research through statutory and conceptual approaches, this study analyzes legislation, legal doctrines, arbitral awards, and relevant scholarly literature using systematic legal interpretation and prescriptive legal reasoning. The findings demonstrate that the legal force of arbitral awards is not derived solely from party autonomy but from the interaction of four complementary dimensions: contractual legitimacy, procedural integrity, institutional recognition through limited judicial supervision, and international legitimacy under the 1958 New York Convention. Judicial oversight functions as a procedural safeguard rather than substantive appellate review, thereby preserving arbitral finality while ensuring legal certainty. This study contributes to contemporary arbitration scholarship by proposing an integrated conceptual framework explaining how privately generated arbitral awards acquire public legal authority within Indonesia's judicial system, thereby strengthening legal certainty, investor confidence, and the effectiveness of commercial dispute resolution.